CORRELATION BETWEEN PATHOLOGY AND EXCESS OF MAXIMUM CONCENTRATION LIMIT OF POLLUTANTS IN THE ENVIRONMENT OF THE REPUBLIC OF DAGESTAN - G. M. Abdurakhmanov; E. S. Erzhapova; M. G. Daudova (Юг России: экология, развитие, 2014)
Abstract. Statistical data from "Indicators of health status of the Republic of Dagestan" for 1999 - 2010 years are presented in the work. The aim of this work was to identify a cause-effect correlation between non-communicable diseases (ischemic heart disease, neuropsychiatric disease, endemic goiter, diabetes, congenital anomalies) and environmental factors in the Republic of Dagestan.Statistical data processing was carried out using the software package Statistica, Microsoft Excel. The Spearman rank correlation coefficient (ρ) was used for identify of correlation between indicators of environmental quality and health of population.Moderate positive correlation is observed between the development of pathology and excess of concentrations of contaminants in drinking water sources. Direct correlations are founded between development of the studied pathologies and excess of concentrations of heavy metals and their mobile forms in soils of the region. Direct correlation is found between excess of concentrations of heavy metals in the pasture vegetation (factorial character) and the morbidity of the population (effective character).